Mother's Knowledge About Nutrition, Disease Infections And Snacking Habits With Nutritional Status Early Age Children In Garessi National Kindergarten - Wijayanti, Lumastari Ajeng; M, Warda; Simatupang, Rumiris; Reffita, Lea Ingne; Nurpratama, Widya Lestari; Palayukan, Safira S'; Pannyiwi, Rahmat; Mildaratu, Mildaratu (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The early childhood group is a group that is vulnerable to nutritional problems. Mothers' low knowledge about nutrition, infectious diseases and poor snacking habits often cause nutritional problems in early childhood. The aim of this research was to determine the relationship between maternal knowledge about nutrition, infectious diseases and snack habits with the nutritional status of early childhood children in Kindergarten in Garessi. This research method is an analytical survey with a cross sectional research design with a total sampling technique. This research was conducted on April 13 2023 using univariate and bivariate analysis with the chi-square test. The research results showed that there was a relationship between maternal knowledge and the nutritional status of early childhood with ap value of 0.004, infectious diseases with the nutritional status of early childhood with ap value of 0.001 and snack habits with the nutritional status of early childhood with ap value of 0.004. The conclusion is that the majority of mothers' knowledge about nutrition is lacking, namely 70.7%, 61% of young children who experience infectious diseases, 56.1% of young children who have bad snack habits and 56.1% of young children who experience abnormal nutritional status namely 53.7%. The research team hopes that mothers will maintain nutritional status in early childhood and prevent children from snacking carelessly.